Atypical Left Ventricular False Chordae Tendineae - Amr Darwish; Priscilla Wessly; Nadeen Faza (Methodist DeBakey Cardiovascular Journal)
An 81-year-old female patient with a history of severe secondary mitral regurgitation, hypertension, and paroxysmal atrial fibrillation was seen by the valve team to determine candidacy for transcatheter edge-to-edge repair of the mitral valve. Two-dimensional biplane imaging showed a transverse basal left ventricle false tendon attached to papillary muscles. The position was concerning for interference during deployment of the mitral clip.